Forest and steppe Priishimje: formation and accumulation of geographical knowledge in XVIII-the beginning of XX centuries (Journal of Geography and Environmental Management, 2019)
In the article change of conceptual approaches in geographical research forest and steppe of Priishimje isconsidered, the basic stages of studying of natural and landscape conditions of area are shown.